AB0600 APREMILAST EFFECTIVENESS IN REFRACTORY ORAL AND GENITAL ULCERS OF BEHÇET'S DISEASE: DATA FROM REAL LIFE SETTINGS. (June 2019) - Lopalco, Giuseppe; Venerito, Vincenzo; Leccese, Pietro; Emmi, Giacomo; Cantarini, Luca; Lascaro, Nancy; Scala, Gerardo DI; Gentileschi, Stefano; Abbruzzese, Anna; Fornaro, Marco; Cacciapaglia, Fabio; Lapadula, Giovanni; et al.
Abstract : Background: Mucocutaneous lesions represent the earliest and the most frequent manifestations of Behçet's disease (BD), and may become disabling leading to substantial effect on quality of life. Recently the efficacy of the small molecule inhibitor of phosphodiesterase 4 apremilast in treating oral and genital ulcers has been shown in a phase 2 trial (1), whereas to date no results from real world data are available. Objectives: The purpose of the present study was to describe our experience with apremilast in treating BD patients with oral and genital ulcers refractory to traditional therapies and previous biologic agents in real life settings Methods: We retrospectively evaluated BD patients according to ICBD (2) and/or ISG (3) criteria who had undergone apremilast therapy (30 mg twice daily) for oral and/or genital ulcers from November 2017 to January 2018 in four different specialized referral Units in Italy (Bari, Firenze, Potenza, Siena). Retrieved data including previous treatments were also collected. Our endpoint was to assess the number of oral and genital ulcers under apremilast treatment. Moreover pain due to ulcers was evaluated with a 100-mm visual-analogue scale (VAS), whereas disease activity was assessed by means of BDCAF score. Paired t-test or Wilcoxon matched-pair signed rank test, if applicable, were used for statistical analysis. Results: Thirteen patients (9 females, 69.2%) with disease duration (mean±SD) of 154.2 ± 167.7 months underwent apremilast treatment because of oral and genital ulcers inadequately responsive to previous immunosuppressant and/or biologic agents. At baseline, patients complained of 1 (1-1) (median (IQR)) oral and 0 (0-1) genital ulcers. At 3-month follow-up (data collected for 12/13 patients) the median number was 0 (0-1) for oral ulcers, and 0 (0-0) for genital ones, showing a significant improvement (p=0.02 for both). However, after 3 months, 3/12 patients (25%) stopped the treatment due to diarrhoea. Thereafter, at 6-month follow-up, a significant improvement of oral ulcers was observed (data collected for 8/13 patients, p=0.03), whereas a statistical significance for genital ulcers was not reached, even in the presence of a positive trend (p=0.07). A notable reduction in VAS and BDCAF scores was observed either after 3 months (p=0.004 and p=0.02, respectively) and 6 months (p=0.01 and p=0.02, respectively). The mean number of relapsing oral and genital ulcers during the first 3 months of therapy was significantly lower than that observed in the four weeks prior to apremilast (p=0.01 for both). Similarly, the average number of the sole oral ulcers appreciably decreased in the first 6 months of therapy (p=0.03). Notably no infections were reported during the whole observation period. Conclusion: Our results, despite the small sample size, corroborate apremilast employment in real-life settings as viable treatment option in BD patients with mucosal involvement multi-refractory to standard treatments. References: [1] Hatemi G, Melikoglu M, Tunc R, Korkmaz C, Turgut Ozturk B, Mat C, et al. Apremilast for behcet's syndrome-a phase 2, placebo-controlled study. N Engl J Med 2015;372:1510-8. [2] International Team for the Revision of the International Criteria for Behcet's D. The international criteria for behcet's disease (icbd): A collaborative study of 27 countries on the sensitivity and specificity of the new criteria. J Eur Acad Dermatol Venereol 2014;28:338-47. [3] O'Neill TW, Rigby AS, Silman AJ, Barnes C. Validation of the international study group criteria for behcet's disease. Br J Rheumatol 1994;33:115-7. Disclosure of Interests: Giuseppe Lopalco Speakers bureau: SOBI, BMS, vincenzo venerito: None declared, Pietro Leccese: None declared, Giacomo Emmi: None declared, Luca Cantarini: None declared, Nancy Lascaro: None declared, Gerardo Di Scala: None declared, Stefano Gentileschi: None declared, Anna Abbruzzese: None declared, Marco Fornaro: None declared, Fabio Cacciapaglia: None declared, Giovanni Lapadula: None declared, Florenzo Iannone Consultant for: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work, Speakers bureau: F Iannone has received consultancy fees and/or speaker honoraria from Pfizer, AbbVie, MSD, BMS, Novartis, Lilly, UCB outside this work